Changes in Strength Properties of Torsion-Loaded Thin-Walled Channel Beam Caused by Constructional Modifications Introduced Based on Statical Analyses - Ireneusz MARKIEWICZ (Engineering Transactions, 2015)
The paper presents results of linear finite element method (FEM) analyses of a thin-walled channel beam in whose central part there are introduced some variants of constructional modifications aimed at improving beam’s ability to carry torsional load. The obtained results show how radically the strength properties of thin-walled structures can be improved by applying simple constructional modifications designed on the basis of the so-called statical analyses. Solutions presented here were taken from the works [2, 5]. Statical analyses allow for finding solutions to constructional problems of complex thin-walled systems, e.g., the systems made of plane elements, well suited to the applied load [2, 5]. They also make it possible to identify cardinal errors in that class of structures and indicate methods of error elimination. Although methods of statical analysis have been studied for a long time, they are still not very popular despite the fact that to use them one only needs to know the fundamentals of statics. The considered problem is important for engineering practice, because the thin-walled channel beams, which are commonly used, exhibit low rigidity to the assumed torsional load.